2016
DOI: 10.1016/j.fishres.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the European lobster ( Homarus gammarus ) in the Irish Sea and implications for the effectiveness of the first British marine protected area

Abstract: Population genetic structure of the European lobster (Homarus gammarus) in the Irish Sea and implications for the effectiveness of the first British marine protected area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 82 publications
2
22
0
Order By: Relevance
“…Our results at a fine geographic scale resemble those obtained by Huserbråten et al (2013), who detected no substantial differentiation throughout a comparable expanse of the Skagerrak, as well as Watson et al (2016), who found no genetic structure across parts of the Irish and Celtic Seas. Our findings indicate that hatchery releases in Cornwall, southwestern UK, are unlikely to exceed the spatial extent of population connectivity by natural dispersal or compromise natural spatial structuring.…”
Section: Discussionsupporting
confidence: 87%
“…Our results at a fine geographic scale resemble those obtained by Huserbråten et al (2013), who detected no substantial differentiation throughout a comparable expanse of the Skagerrak, as well as Watson et al (2016), who found no genetic structure across parts of the Irish and Celtic Seas. Our findings indicate that hatchery releases in Cornwall, southwestern UK, are unlikely to exceed the spatial extent of population connectivity by natural dispersal or compromise natural spatial structuring.…”
Section: Discussionsupporting
confidence: 87%
“…For example, Watson et al. () studied the population genetic structure of the European lobster in the Irish Sea jointly with the estimation of N e for nine sampling locations. For six locations using the LD method, N e was estimated to be negative (with confidence intervals including infinity) and thus interpreted to be infinite.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, N e was considered difficult to estimate but this situation has changed (Leberg, ; Schwartz, Tallmon, & Luikart, ). As a consequence, N e is nowadays commonly estimated for varied marine taxa: mammals (DeWoody et al., ), crustaceans (Watson, McKeown, Coscia, Wootton, & Ironside, ), corals (Holland, Jenkins, & Stevens, ) and fishes (Laconcha et al., ; Pita, Pérez, Velasco, & Presa, ; Zhivotovsky et al., ). Among commercial fish species, both target (Montes et al., ; Poulsen, Nielsen, Schierup, Loeschcke, & GrøNkjaer, ) and by‐catch species (Chevolot, Ellis, Rijnsdorp, Stam, & Olsen, ) have been studied, representing a wide range of life history strategies, habitats, population structures but also census population sizes (i.e., total number of individuals in the population including immatures, denoted N ), from hundreds to billions of individuals.…”
Section: Ne Estimation For Large Marine Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, genetic diversity and population structure has been investigated in H. gammarus using traditional molecular markers including random amplification of polymorphic DNA (RAPDs) (Ulrich et al 2001), allozymes (Jorstad et al 2005), mtDNA restriction fragment length polymorphisms (RFLPs) (Triantafyllidis et al 2005) and microsatellites (Huserbraten et al 2013;Watson et al 2016;Ellis et al 2017). However, single nucleotide polymorphisms (SNPs) are becoming the marker of choice in molecular ecology studies, particularly for non-model organisms without a well-annotated genome, because they are (i) abundant and generally widespread in the genome, (ii) eligible for high-throughput screening and automation, and (iii) reproducible across labs (Seeb et al 2011).…”
mentioning
confidence: 99%